(untitled) (Sustainability in Debate, 2017)
The stimulation of rural development requires tailoring public policies in order to fit the demands of communities and of civil society organizations, thus recognizing the specificities of each territory and offering development tools that attend family farmers’ needs. This article aims to analyze the effects that the National Program for Food Acquisition ”“ PAA (in Portuguese) has on family farming through a case study at Rio Branco do Sul and Itaperuçu, munipalities of the Ribeira Valley, in the Brazilian State of Parana. Results show that the Program has a strategic role in fostering food production in local family farms, while ensuring price fairness, agricultural biodiversity and traditional foods. PAA was also discovered to involve farmers in the local market chain in spite of the specific changes that should be applied. It is concluded that the situation of local family farming has improved since the 1970s. Although beneficiaries remain highly dependent on the Program, the improvement regarding public policies and funding support for family farmers is evident.